Magnetic Bearings Theory and Applications - Polajzer, Bostjan (IntechOpen, 2010)
The term magnetic bearings refers to devices that provide stable suspension of a rotor. Because of the contact-less motion of the rotor, magnetic bearings offer many advantages for various applications. Commercial applications include compressors, centrifuges, high-speed turbines, energy-storage flywheels, high-precision machine tools, etc. Magnetic bearings are a typical mechatronic product. Thus, a great deal of knowledge is necessary for its design, construction and operation. This book is a collection of writings on magnetic bearings, presented in fragments and divided into six chapters. Hopefully, this book will provide not only an introduction but also a number of key aspects of magnetic bearings theory and applications. Last but not least, the presented content is free, which is of great importance, especially for young researcher and engineers in the field.